Rampant use of Nimesulide in Pakistan, a drug associated with hepatotoxicity - Muhammad Umar; Muhammad Ahrar Bin Naeem (Journal of the Pakistan Medical Association, 2023)
Madam, Nimesulide is a drug very commonly used in Pakistan. It is a non-steroidal anti-inflammatory drug (NSAID) with selectivity for cyclooxygenase-2 (COX-2) (1). Nimesulide is used as an analgesic, anti-inflammatory, and antipyretic (2). This drug which was first introduced in Italy, has been successfully marketed in more than 50 countries except for the US (3). Moreover, as a result of its extensive and rapid absorption, it allows effective pain control. Nimesulide has been known to induce hepatotoxicity (4), with the first case being reported in 1997, followed by many reports of severe or even fatal cases of liver injury. Consequently, it was restricted or withheld from the market in Spain and France since 2002, with other countries following suit. Recent publications point to the formation of reactive metabolites leading to liver damage. Some factors highly prevalent in our demographics, such as metabolic syndrome, also increase the risk of developing hepatotoxicity (5). These factors alarm us to increase awareness campaigns directed at restricting the use of Nimesulide and potentially leading to the ban of this drug. Nimesulide, NSAIDs, antibiotics and most other drugs are available over the counter in Pakistan. Self-medication of these drugs is a common practice. Measures are needed to restrict the availability of such drugs, the extensive use of which can lead to antibiotic resistance and potentially lethal side effects. These drugs should only be dispensed upon proper prescription, so as to achieve better control in the population.